GROWTH PATTERN OF BIGFIN REEF SQUID (Sepioteuthis lessoniana) IN KOLAKA WATERS, SOUTHEAST SULAWESI - Muhammad Gazali; Putri Meira Shyiang Sri (Universitas Mataram, 2026)
Length–weight relationships using the allometric model W=aLb are widely applied to describe growth patterns in aquatic organisms. This study analyzed the length-weight relationship of bigfin reef squid (Sepioteuthis lessoniana) in Kolaka Waters, Southeast Sulawesi. Samples were randomly collected from fishermen’s catches in Tanggetada District during July–December 2025, with measurements of total length, mantle length, and body weight. The results showed that the population size structure was dominated by medium to large sized individuals. The length–weight relationship yielded a growth coefficient b<3, indicating a negative allometric growth pattern, where length increases faster than body weight. Although the allometric model effectively describes general growth patterns, its application across the entire size range should be treated with caution due to potential bias, particularly at extreme sizes. These findings provide important biological information to support the sustainable management of S. lessoniana in Kolaka Water.